2021
DOI: 10.21270/archi.v10i8.5284
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do nível de conhecimento de escolares do ensino médio sobre o câncer bucal

Abstract: O conhecimento da relação entre o câncer de boca e fatores relacionados ao estilo de vida, como o tabagismo, etilismo e a exposição solar são conhecidos na comunidade científica, entretanto, este conhecimento também deve ser disseminado nos diversos estratos da população. Objetivou-se avaliar o conhecimento de escolares do 3º ano do ensino médio de um município de médio porte do Estado de São Paulo sobre o câncer de boca. Método: Estudo transversal com 1012 escolares da rede pública de ensino de Araçatuba-SP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The sun exposition was identified in 23.1% and only 1.2% trauma as risk factors. These results bring us an alert that knowledge about relevant risk factors is not of a broad domain in this age group, consistent with previous studies that also identified a lack of knowledge of risk factors [17][18][19][20][21][22]24 .…”
Section: Miscellaneoussupporting
confidence: 91%
See 1 more Smart Citation
“…The sun exposition was identified in 23.1% and only 1.2% trauma as risk factors. These results bring us an alert that knowledge about relevant risk factors is not of a broad domain in this age group, consistent with previous studies that also identified a lack of knowledge of risk factors [17][18][19][20][21][22]24 .…”
Section: Miscellaneoussupporting
confidence: 91%
“…This "oncological universe" is still a very unknown area for this age group. There are few published articles about the level of knowledge about cancer in this age group, and head and neck cancer, in general, has not been the object of much evaluation, being found in the literature mainly studies on cancer of the oral cavity and skin [17][18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%